Association of ABO Blood Groups with Secretor Status among Healthy Blood Donors - Nahar, Kamrun; Binni, Subrina Yeasmin; Nine, S M A Zulker (Community Based Medical Journal, 2025)
The ABO blood group system and secretor status are genetically determined polymorphic traits with potential associations to various health conditions. Understanding the distribution of secretor status across different ABO blood groups in a healthy population is crucial for genetic and epidemiological studies. This study aims to determine the association between ABO blood groups and secretor status among healthy blood donors in Bangladesh. This prospective cross-sectional study was conducted in the Department of Transfusion Medicine of Committee of Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, a tertiary level hospital in Bangladesh, between January and December 2023. A purposive sampling technique was used to recruit a total of 187 healthy blood donors. ABO blood groups were determined using standard haemagglutination tests. Secretor status was determined by detecting the presence of ABH antigens in saliva. We found blood group ‘B’ (36.9%) as the most prevalent, followed by ‘O’ (31.6%). Secretors (76.5%) outnumbered non-secretors (23.5%), with the highest secretor frequency in group ‘O’ (82.8%). ABO blood groups showed a significant association with secretor status (χ²=6.24, p=0.044). Rh-positive individuals had more secretors (77.3%). Blood group ‘A’ had the highest odds of being secretors (OR=1.85). Our study confirms a significant association between ABO blood groups and secretor status among healthy donors, with group ‘O’ having the highest secretor frequency. These findings may aid in understanding genetic and immunological interactions linked to blood group antigens and secretor phenotypes. CBMJ 2025 July: vol. 14 no. 02 P:34-39